The API Generation program: Biomarker phenotyping of cognitively unimpaired participants screened in Generation study 1 and Generation study 2: Alzheimer's Prevention Initiative (API) Generation program: Baseline characteristics and umibecestat results during treatment and follow‐up. (7th December 2020) - Rouzade‐Dominguez, Marie‐Laure; Riviere, Marie‐Emmanuelle; Borowsky, Beth; Liu, Fonda; Cazorla, Pilar; Quinn, Matt; Seneca, Nicholas; Neumann, Ulf; Eichenlaub, Udo; Chien, Yuchen; Viglietta, Vissia; Reiman, Eric M.; et al.
Abstract: Background: API Generation Program evaluated the effectiveness of the BACE1 inhibitor umibecestat and the active immunotherapy CAD106 in delaying the onset of AD symptoms in APOE4 carriers. Data from imaging (vMRI and PET scans), and fluid biomarkers (blood and CSF) were collected during the 12‐week Screening phase. In this presentation, we will summarize results across the two studies and investigate the relationships between the various biomarkers and key baseline characteristics. Method: Amyloid levels were assessed via CSF and/or Amyloid PET scan in both studies for the APOE4 carriers. Generation Study 2 enrolled heterozygotes based on the following elevated amyloid inclusion criteria: Roche Elecsys® CSF p‐Tau/Abeta42 ratio > 0.024 and/or PET scans with any of the 3 amyloid F 18 tracers (florbetapir, flutemetamol or florbetaben). If the centralized visual read of PET scan was negative, the SUVr was calculated (cortical composite in reference to whole cerebellum) for the three tracers in order to assess borderline cases. Thresholds for amyloid positivity equivalent to SUVR of 1.1 with florbetapir were used for the final decision on inclusion. Result: Across both studies, over 500 lumbar punctures, 2700 amyloid PET scans and about 150 tau PET scans (conducted using flortaucipir) were performed. In Generation Study 1, over 200 FDG PET scans were also performed. Participants underwent amyloid testing during screening, blood sampling (plasma and serum) and underwent MRI scans for safety and to measure brain volumes. All baseline biomarker data will be presented, including available concentrations from CSF Tau/p‐Tau/Aβ42/Aβ40 along with the eligibility ratio for pTau/ab42. In about 150 participants, concordance between elevated/non elevated amyloid status by CSF and PET (using centiloids) will be shown. Baseline brain volume (whole brain and hippocampus) will be summarized for the different co‐variates (age, sex, cognition, genotype and amyloid status). Correlations among the various fluid biomarkers and imaging will be discussed. Conclusion: These data describe the biomarker signature of the world's largest cohort of cognitively unimpaired APOE4 carriers with and without elevated amyloid. The anonymized study data, biomarker samples as well as images collected will be shared with the scientific community after study completion and reporting. ELECSYS is a registered trademark of Roche.